2008
DOI: 10.21608/jssae.2008.166878
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antimicrobial and Antioxidant Potential of Tea and Carob Extracts in Buffalo Butter

Abstract: The present study was carried out to evaluate the antimicrobial and antioxidant effects of black tea extract (BTE), green tea extract (GTE) and carob extract (CRE) in buffalo butter during storage at 4±1ºC for 12 weeks and compare to synthetic phenolic compound butylated hydroxytoluene, (BHT). The antibacterial effect and minimal inhibitory concentration (MIC) of extract against Listeria monocytogenes were studied. The effectiveness of these extracts (0.025 -0.05%) in butter made from pasteurized cream were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
1
1
1
Order By: Relevance
“…In Table 2 the PVs of the examined samples were between 0.1 and 0.9 mEq O2/kg in pasteurized butter with an average of 0.39±0.02 meq O2/ kg which was like the results obtained by Koyuncu and Tuncturk (2017) (2009). While for Falahy butter samples, the PVs were found to be 0.1 to 1.3 mEq O2/kg in Falahy butter samples with an average of 0.44±0.03 meq O2/ kg The obtained result was like that recorded by Ramadan et al (2009) and Simsek (2011) It is worth mentioning that no significant differences were observed between peroxide values of pasteurized and Falahy butter in this study which were in good agreement with the findings given by Veberg et al (2006) andSamet bali et al (2009), who indicated that fresh butter showed an only very low concentration of peroxides.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…In Table 2 the PVs of the examined samples were between 0.1 and 0.9 mEq O2/kg in pasteurized butter with an average of 0.39±0.02 meq O2/ kg which was like the results obtained by Koyuncu and Tuncturk (2017) (2009). While for Falahy butter samples, the PVs were found to be 0.1 to 1.3 mEq O2/kg in Falahy butter samples with an average of 0.44±0.03 meq O2/ kg The obtained result was like that recorded by Ramadan et al (2009) and Simsek (2011) It is worth mentioning that no significant differences were observed between peroxide values of pasteurized and Falahy butter in this study which were in good agreement with the findings given by Veberg et al (2006) andSamet bali et al (2009), who indicated that fresh butter showed an only very low concentration of peroxides.…”
Section: Resultssupporting
confidence: 81%
“…These results were higher than that obtained by El-Safty et al (2017), Koyuncu and Tuncturk (2017) and Méndez-Cid et al (2017). For Falahy butter samples, the TBA was between 0.09 and 0.88 with an average of 0.51±0.02 mg MDA / Kg which is higher than that recorded by Ramadan et al (2009) and Simsek (2011).…”
Section: Resultscontrasting
confidence: 59%
See 1 more Smart Citation